Kajian Pengobatan Dengue Haemoragic Fever (DHF) di Rumah Sakit Pendidikan Universitas Mataram - Dwi Monika Ningrum; Denih Agus Agus Setia Permana (UNIVERSITAS MUHAMMADIYAH MATARAM, 2023)
Dengue Hemorrhagic Fever (DHF) has become a worldwide problem. Dengue Haemoraggic Fever (DHF) is a disease caused by the dengue virus through the bite of the Aedes aegypti mosquito. DHF has a high mortality rate, so there is a need for appropriate therapy to reduce morbidity. This study aims to determine how the rationality of treatment in patients with Dangue Haemorraggic Fever (DHF) at the University Hospital of Mataram for the Period January - June 2020. This study is a non-experimental descriptive study, where data was taken retrospectively obtained from records. Medical records of Dengue Haemoraggic Fever (DHF) patients at the Inpatient Installation of Mataram University Hospital Period January - June 2020. The sampling technique used was purposive sampling, and 40 medical records were obtained. This research was conducted by looking at the rationality of treatment based on the right indication, the right patient, the right drug, and the right dose. The data obtained were compared with the basic guidelines for the management of DHF treatment therapy from the Ministry of Health of the Republic of Indonesia in 2004. The results showed the rationality of DHF treatment seen from several aspects, namely in the use of analgesic-antipyretic drugs and maintenance fluids, appropriate indications in the use of analgesic-antipyretic drugs and maintenance fluid obtained a percentage of 100%. In addition, the exact data on antipyretic analgesic drugs was 82.5%, the exact dose of antipyretic analgesics was 55%